Comments on the updated recommendations of the American College of Rheumatology (ACR) for the treatment of gout. Lifestyle (part 2) - M. S. Eliseev (Современная ревматология)
Updated ACR recommendations for the treatment of gout concerning lifestyle are discussed. Factors related to a lifestyle, above all food habits, for many years were of leading importance in the treatment of patients with gout, even after application of effective drugs. The authors of the updated ACR recommendations for the first time offered to reconsider the role of environmental factors in the genesis of gout and objectively assess the possibility of its non-drug treatment. On the one hand, regardless of the activity of the disease, the need for restrictions of the alcohol, purine-rich products and fructose-containing beverages, as well as the decrease of body weight in obese patients and vitamin C usage unviability are confirmed. On the other hand, these recommendations are conditional. Their new version of ACR recommendations is significantly different from both its previous version and other international and national recommendations, including recommendations on the diagnosis and treatment of gout used in the Russian Federation.